2010
DOI: 10.1097/psy.0b013e3181dbff97
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Association of Anxiety Post Myocardial Infarction With Mortality and New Cardiac Events: A Meta-Analysis

Abstract: Post-MI anxiety is associated with a 36% increased risk of adverse cardiac outcomes in bivariate analyses. Because the existing literature is small and contains several limitations, more research is needed to evaluate the association of anxiety and prognosis in patients with MI and to assess the extent to which this association is independent of clinical variables, such as disease severity, and other psychological variables, especially depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
236
2
23

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(270 citation statements)
references
References 51 publications
9
236
2
23
Order By: Relevance
“…The relevance of the presence of anxiety and depression in cardiac patients has repeatedly been shown in systematic reviews; both are associated with higher death rates and poorer prognoses in general in cardiovascular disease (3)(4)(5).…”
mentioning
confidence: 89%
“…The relevance of the presence of anxiety and depression in cardiac patients has repeatedly been shown in systematic reviews; both are associated with higher death rates and poorer prognoses in general in cardiovascular disease (3)(4)(5).…”
mentioning
confidence: 89%
“…41,50,53 A An nk ks si iy ye et te e Anksiyete, kısa ve uzun dönem iyileşmeyi etkileyebilir. Negatif duygular ya da stresörler [platelet, makrofaj hücre aktivasyonu ve lipit seviyesinde artma, kalp hızında ve kan basıncı (KB)'nda artma ve miyokardiyal oksijen sunumunda azalma gibi yanıtlar) psikolojik değişikliğin tetiklenmesi ile nöroendokrin sistemi aktive eder.…”
Section: Negati̇f Etki̇unclassified
“…Bir meta-analizde, 11 yıllık takip sonunda anksiyeteli bireylerde diğer prognostik faktörlerden bağımsız olarak KKH riskinin 1,3 kat, kardiyak mortalite riskinin ise 1,5 kat arttığı gösterilmiştir. 53 Diğer bir meta-analizde de anksiyeteli olan hastaların hastalık süreci ve seyrinin daha kötü olduğu saptanmıştır. Özellikle, anksiyete riski bütün sebeplerden mortalite için 1,5 kat, kardiyak mortalite için 1,2 kat ve yeni kardiyak sorunlar için 1,7 kat artmıştır.…”
Section: Negati̇f Etki̇unclassified
See 1 more Smart Citation
“…Notably however, the meta-analytic estimate for the association with CHD was not adjusted for depression. A further meta-analysis examining the prognostic association of anxiety in post-MI patients found that elevated anxiety was predictive of allcause mortality, cardiac mortality and new cardiac events at three years follow-up [116]. More recently a study of 1411 patients with CHD found that while both depression and anxiety predicted all-cause mortality 10 years post-PCI, anxiety conferred no additional risk in the case of co-morbid depression [117].…”
Section: Anxietymentioning
confidence: 99%